2021
DOI: 10.3390/agriculture11010062
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage on Physiological Properties, Chemical Composition, and Bioactive Compounds on Cactus Pear Fruit (Opuntia ficus-indica (L.) Mill.)

Abstract: Cactus pear (Opuntia ficus-indica (L.) Mill.) fruit from ‘Orito’ cultivar were stored at 2 °C and 90% RH for 28 days plus three days at 20 °C (shelf life, SL). This research analysed the changes in fruit quality parameters (weight loss, firmness, color, titratable acidity, and total soluble solids), ethylene production, respiration rate, antioxidant activity and bioactive compounds (total phenols and carotenoids) of cactus pear fruit during cold and shelf life storage. Under cold conditions, CO2 production dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(49 reference statements)
1
15
0
Order By: Relevance
“…Although prickly pear was classified as a non-climacteric fruit, classification of climacteric and non-climacteric fruit is not absolute, and genotypes and cultivars of some species can show both patterns [ 11 , 12 ]. ‘Orito’ fruit, the commercial Spanish cultivar studied in this work, showed a suppressed climacteric pattern in ethylene production and respiration rate similar to some cultivars of plum, which showed no increase in respiration rate or in ethylene production associated with ripening [ 13 , 14 , 15 ]. In a previous work we demonstrated that ‘Orito’ fruit maintained its quality parameters in desirable values up to 28 days, both in cold conditions (2 °C, 85–90% relative humidity, RH) and during shelf-life storage, whereas the total phenolic content increased during the shelf life conditions [ 13 ].…”
Section: Introductionmentioning
confidence: 84%
“…Although prickly pear was classified as a non-climacteric fruit, classification of climacteric and non-climacteric fruit is not absolute, and genotypes and cultivars of some species can show both patterns [ 11 , 12 ]. ‘Orito’ fruit, the commercial Spanish cultivar studied in this work, showed a suppressed climacteric pattern in ethylene production and respiration rate similar to some cultivars of plum, which showed no increase in respiration rate or in ethylene production associated with ripening [ 13 , 14 , 15 ]. In a previous work we demonstrated that ‘Orito’ fruit maintained its quality parameters in desirable values up to 28 days, both in cold conditions (2 °C, 85–90% relative humidity, RH) and during shelf-life storage, whereas the total phenolic content increased during the shelf life conditions [ 13 ].…”
Section: Introductionmentioning
confidence: 84%
“…Cactus pear is a non-climacteric fruit, characterized by a quite short postharvest life due to an intrinsic predisposition to physical damage as well as high metabolic activity; fruit firmness changes during postharvest storage life are usually due to dehydration and changes in the components of the middle lamella and primary cell wall, which causes fruit softening [28]. Indeed, the combined action of cell wall hydrolyzing enzymes results in loss of integrity of the cell wall by the disassembly of the cellulose-hemicellulose network [29].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-eight days later, TSS concentration was of 11.4 and 12° Brix for Blanca Cristalina and Esmeralda pears [112]. Cactus pears from the "Orito" cultivar presented 14.9°Brix after harvest and 14°Brix after 28 days later [111]. Blanca Cristalina TA values remained constant at 0.25% during the three months, so fruits remain acid and fruit acceptance high [111].…”
Section: Prickly Pear Physicochemical Analyses and Measurementsmentioning
confidence: 98%
“…Cactus pears from the "Orito" cultivar presented 14.9°Brix after harvest and 14°Brix after 28 days later [111]. Blanca Cristalina TA values remained constant at 0.25% during the three months, so fruits remain acid and fruit acceptance high [111]. Blanca Cristalina and Esmeralda presented 0.27 and 0.29% of citric acid at harvest, respectively.…”
Section: Prickly Pear Physicochemical Analyses and Measurementsmentioning
confidence: 99%
See 1 more Smart Citation